Da Vinci robot-assisted laparoscopic retroperitoneal debridement for lumbar septic spondylodiscitis: A two-case report - Ye, Jichao; Liu, Hao; Hu, Xumin; Li, Jinteng; Gao, Liangbin; Tang, Yong (Frontiers in Surgery, 2022)
The anterior approach is one of the widely used surgical treatments for lumbar spondylodiscitis, but it has the disadvantages of large trauma and a high incidence of complications. Our experiences suggested that the laparoscopic retroperitoneal approach could be effective to overcome those disadvantages of the anterior approach. Herein, we report two cases of successfully treated lumbar pyogenic spondylodiscitis using a robot-assisted laparoscopic retroperitoneal approach. The technique utilizes a robot that allows a laparoscopic retroperitoneal approach while offering excellent high-definition images of three-dimensional vision. After the operation, both patients achieved good formation and fusion of the vertebrae. Preliminary evidence suggests that the robot-assisted laparoscopic retroperitoneal approach may be feasible for the treatment of lumbar spondylodiscitis.